Biased pathogenic assertions of loss of function variants challenge molecular diagnosis of admixed individuals. Issue 3 (29th June 2021) - Naslavsky, Michel S.; Scliar, Marília O.; Nunes, Kelly; Wang, Jaqueline Y. T.; Yamamoto, Guilherme L.; Guio, Heinner; Tarazona‐Santos, Eduardo; Duarte, Yeda A. O.; Passos‐Bueno, Maria Rita; Meyer, Diogo; Zatz, Mayana
Abstract: Diagnosis of individuals affected by monogenic disorders was significantly improved by next‐generation sequencing targeting clinically relevant genes. Whole exomes yield a large number of variants that require several filtering steps, prioritization, and pathogenicity classification. Among the criteria recommended by ACMG, those that rely on population databases critically affect analyses of individuals with underrepresented ancestries. Population‐specific allelic frequencies need consideration when characterizing potential deleteriousness of variants. An orthogonal input for classification is annotation of variants previously classified as pathogenic as a criterion that provide supporting evidence widely sourced at ClinVar. We used a whole‐genome dataset from a census‐based cohort of 1, 171 elderly individuals from São Paulo, Brazil, highly admixed, and unaffected by severe monogenic disorders, to investigate if pathogenic assertions in ClinVar are enriched with higher proportions of European ancestry, indicating bias. Potential loss of function (pLOF) variants were filtered from 4, 250 genes associated with Mendelian disorders and annotated with ClinVar assertions. Over 1, 800 single nucleotide pLOF variants were included, 381 had non‐benign assertions. Among carriers ( N = 463), average European ancestry was significantly higher than noncarriers ( N = 708; p = .011). pLOFs in genomic contexts of non‐European local ancestries were nearly three times less likely to have any ClinVar entry (OR = 0.353; p <.0001). Independent pathogenicity assertions are useful for variant classification in molecular diagnosis. However, European overrepresentation of assertions can promote distortions when classifying variants in non‐European individuals, even in admixed samples with a relatively high proportion of European ancestry. The investigation and deposit of clinically relevant findings of diverse populations is fundamental improve this scenario.